To what extent can local-led innovation platforms tackle complex agricultural development challenges? Insights from Madagascar. Issue 2 (15th March 2023) - Audouin, Sarah; Raharison, Tahina; Rabesoa, Joanna; Noharinjanahary, Edson Samuel; Ranaivoson, Rado; Triomphe, Bernard
ABSTRACT: Purpose: To investigate the emergence and specificities of local-led innovation platforms (IPs) in Madagascar and contrast them with neighbouring research-led IPs. Design/methodology/approach: We developed a multi-disciplinary framework combining insights from the literature on IP, innovation support services, and innovative networks. Using an exploratory multiple case study approach, we used this framework to analyse eight IPs in Madagascar. Findings: (i) local-led IPs are problem oriented, (ii) there is a gap between the stated objectives of the IPs and their activities, (iii) their significant shortcomings result from weak or lacking inter-organisational management practices. Practical Implications: We propose concrete avenues for strengthening local-led IPs by building their capacity to innovate at the individual, organisational and network levels. Theoretical Implications: We contribute to refining IP assessment methods with an operational framework based on a small subset of variables, focusing on activities, shortcomings, and inter-organisational management practices. We also call for further research into innovation network capacities. Originality/Value: Our study sheds light on less documented local-led IPs. From a critical point of view, it shows that, despite the interest they attract among donors, local-led IPs suffer from specific weaknesses and require substantial support, especially when they operate in weak enabling environments.